The Effect of Islamic Selection, Training and Job Rotation on Employee Performance PT Rampai Berkah Bersama - Rusli, Lathiefa; Firmansyah, Lutfi Aditya; Firmansah, Yayan (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2024)
Human Resources are required to organize and manage the Company. Companies have to improve the quality of human resources training, starting from selection, training and job rotation. This study aims to determine the effect of Islamic Selection, Training and Job rotation on Employee Performance of PT Rampai Berkah Bersama. This research uses descriptive quantitative by distributing questionnaires to 73 employees of PT Rampai Berkah Bersama, then analyzed using multiple regression analysis. The results showed that partially Islamic selection did not affect the performance of employees of PT Rampai Berkah Bersama, which was indicated by the calculated T value of 0.454>T table 0.230 or a p-value of 0.651>0.05. Training has a significant effect on the performance of employees of PT Rampai Berkah Bersama, which is indicated by the T value of 4.081>T table 0.230 or a p-value of 0.000<0.05. Work rotation has a significant effect on employee performance of PT Rampai Berkah Bersama, which is indicated by the T value of 5.478>T table 0.230 or a p-value of 0.000<0.05. Simultaneously all independent variables (Islamic Selection, Training and Job rotation) have a positive and significant effect on the performance of employees of PT Rampai Berkah Bersama. The results showed no influence between Islamic Selection on the performance of employees of PT Rampai Berkah Bersama, the company should optimize the selection process during interviews, and also be more thorough in the administrative process. Also increase employee training and rotation so that the performance of PT Rampai Berkah Bersama employees can increase.